The quality of buck semen after feed additive minoxvit administration - Anita Hafid; Riasari Gail Sianturi; Diana Andrianita Kusumaningrum; Yeni Widiawati; Anneke Anggraeni; Ferdy Saputra (Universitas Sebelas Maret, 2021)
Objective: Reproduction and nutritional status is closely related. Nutritional deficiency or insufficiency directly affects reproductive efficiency. Deficiency of nutrition could affect the sperm quality and the ability to fertilize. The objective of this study was to evaluate the effect of feed additive (Minoxvit) on semen quality of buck.Methods: This study used 6 sexually mature bucks, aged 1.5 years old. The bucks were fed daily with 3 kg of freshly chopped king grass, 1 kg of Legume (Calliandra sp.), and 500 g of concentrate. Three bucks were given Minoxvit by 1.25 g/day in the concentrate, while three other bucks were considered as control. Semen was evaluated once a week for 49 days. Semen was evaluated macroscopically and microscopically. The macroscopic evaluation consisted of volume, color, and consistency of semen, while microscopic evaluation consisted of mass motility, sperm motility, viability, and sperm concentration. Data were analyzed using Completely Randomized Design with Tukey test.Results: The result showed significantly different (P<0,05) in which bucks semen in Minoxvit addition group had higher semen volume (0.75 ml vs 0.54 ml), mass motility (3.32 vs 2.67), sperm motility (70% vs 58 %), sperm viability (86.67% vs 79.19%), and sperm consentration (2,6x109 mL vs 1,7x109 mL).Conclusions: This study concludes that the addition of Minoxvit has a positive influence on the quality of buck sperms providing volume, mass motility, individual motility, viability, and concentration of the sperm.